Creating Self-Efficacious Special Educators through Mentoring during Teacher Preparation - Lombardo-Graves, Mary M. (Journal of the American Academy of Special Education Professionals, 2019)
The purpose of this study was to examine the effects of a specific mentoring intervention on the teaching self-efficacy of pre-service special education teacher candidates. A Special Educators Efficacy Scale (SEES) was developed to measure self-efficacy for the initial skill set required for novice special educators. A two-group, pre-test/post-test design was used to compare the special education teaching self-efficacy scores between the intervention and comparison group. The self-efficacy scores reported by 245 pre-service special education candidates from two universities were analyzed (intervention group, N = 43; comparison group, N = 202) before and after a 10-week mentoring intervention. ANCOVA findings indicated a statistically significant difference across all subscales between groups while controlling for the pre-test scores. The analysis of demographic characteristics such as age and grade level did not reveal any statistically significant differences between groups.